Capability of separate determination of colored components in their mixture using digital RGB-colorimetry - Khimchenko, S.V.; Eksperiandova, L.P. (Functional Materials, 2016)
One of the inalienable steps in manufacturing of functional materials is the operational control of traces of toxic heavy metals such as Fe(III) and Co(II) which are present in industrial waste water. The optimal variant for requirements of the analysis in-situ and "green chemistry" is using of environmentally friendly sorbents for preconcentration with simple procurable and portable equipment. Colorimetric characteristics of colored components on the example of thiocyanate complexes of Fe(III) and Co(II) by means of digital RGB-colorimetry have been studied. Algorithm for the colorimetric determination of each of the said components at their joint presence in water using measurements of only three color parameters of the colored mixture was developed. Separation factor of the analytical signal is estimated.